2014
DOI: 10.5539/jms.v4n4p167
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Environmental Manufacturing Practice (SEMP) and Firm Performance: Moderating Role of Environmental Regulation

Abstract: Theoretical evidence shows that a considerable amount of attention has been given to environmental issues in academic researches in the past years and the link between sustainable environmental practices and firm performance remains inconclusive. One of the reasons for this inconsistent relationship is due to the increasing regulatory requirements of the environmental sustainable practices which have become increasingly stringent on yearly basis. This study investigates the moderating effect of environmental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The data obtained through the study supports the notion that when effective regulations are put in place, there is a noticeable improvement in the overall environmental conditions. The findings of this study are relevant to the study conducted by Adebambo et al (2014). The findings of their study indicated that there is a positive and significant influence between government regulation on environmental performance.…”
Section: Discussionsupporting
confidence: 51%
“…The data obtained through the study supports the notion that when effective regulations are put in place, there is a noticeable improvement in the overall environmental conditions. The findings of this study are relevant to the study conducted by Adebambo et al (2014). The findings of their study indicated that there is a positive and significant influence between government regulation on environmental performance.…”
Section: Discussionsupporting
confidence: 51%
“…Previous literatures on sustainability issues are evidenced on the various types of studies that have been embarked upon in particular from the standpoints of the developing and developed countries with respect to the many dimensions of sustainability. They include financial disclosures (Imeokparia and Olagunju, 2013;Madawaki, 2014) environmental management, performance and disclosures (Adebambo et al, 2014;Chaklader and Gulati, 2015) and social and environmental disclosures (Adhikari et al, 2015). Others are governance on social reporting (Haniffa and Cooke, 2005;Orij, 2010) legal institutions on corporate social disclosure (Adelopo et al, 2013) and legal origin or systems on financial disclosures (Hope, 2003).…”
Section: Sustainability Initiatives (Si)mentioning
confidence: 99%
“…Results indicated that manufacturers in Malaysia experience high external pressures such as regulatory and marketing/customer pressures. Moreover, in Malaysia, Adebambo et al (2014) used environmental regulations as the moderating variable for the relationship between sustainable environmental practices and firm performance. Vanalle et al (2017) identified that institutional pressures influence the supply chain to pursue GSCM practices.…”
Section: Institutional Pressurementioning
confidence: 99%